Co-carbonization of a mixture of waste insulation electric cables (WIEC) and lignocellulosic waste, for the removal of chlorine: Biochar properties and their behaviors. (15th July 2022) - Mota-Panizio, R.; Hermoso-Orzáez, M.J.; Carmo-Calado, L.; Calado, H.; Goncalves, M.M.; Brito, P.
Highlights: Waste insulation electrical cables (WIEC) can be recovered thermochemical, in combustion or gasification processes, however, these residues have a high chlorine content in their composition, which can cause damage to thermochemical recovery equipment. This work has the objective to study the effects of the temperatures and the mixtures proportions in the carbonizations and co-carbonizations of waste insulation electrical cables with lignocellulosic waste. The co-carbonization tests produced high-quality biochars and were able to significantly remove the amount of chlorine present in the materials. The synergistic effect between WIEC and lignocellulosic biomass was verified, laying the foundations for the next study on optimization of parameters and valorization of the chars obtained in the thermal gasification process. Abstract: The valorization of noble metals from the recycling of electric cables, generates a negative effect with regard to the production of polymeric residues, mainly composed of polyvinyl chloride (PVC), polyethylene (PE) and polypropylene (PP). Waste insulation electrical cables (WIEC) can be recovered thermochemical, in combustion or gasification processes, however, these residues have a high chlorine content in their composition, which can cause damage to thermochemical recovery equipment, if used in gross. This work has the objective to study the effects of the temperatures and the mixtures proportions in the carbonizations and co-carbonizations of waste insulation electrical cables with lignocellulosic waste. The mixtures with different waste insulation electrical cables ratios (100, 75, 50, 25 and 0%), were carbonized at 300 °C and retention time of 30 min and showed chlorine removals above 66%. With the 50% waste insulation electrical cables mixture having a removal below the 25% and 0% mixtures (with 100% chlorine removals), the dechlorination being 84.9%. Tests were also carried out with 50:50 mixtures of waste insulation electrical cables and lignocellulosic waste for temperatures of 275, 300 and 325 °C with retention times of 30, 45 and 60 min. After being subjected to an acetone wash, it was obtaining removals of around 80%. For the mixture at 300 °C and 30 min (M300-30), mixture at 300 °C and 60 min (M300-60) and the mixture at 325 °C and 30 min (M325-30) thus having the best chlorine removals, being 81%, 81.9% and 86.7% respectively. For the determination of these mixtures, immediate analysis, approximate analysis, fluorescence x-ray and calorific value tests were performed. With the analyzes carried out, it was possible to perform calculations of the kinetics of the behavior of biochars. It was possible to observe that with the increase in temperature the activation energy of the biochar reduced, that is, the biochar decreased adsorption.